Residency Prep Course Instills Confidence in Interns: Residency Prep Course Instills Confidence in Interns - Winter, Kelly; Quinn, Karson; Helmer, Stephen; McBoyle, Marilee (Kansas Journal of Medicine, 2021)
Introduction.  Physicians entering surgical residency often feel unprepared for tasks expected of them beginning July 1, including responding to pages, writing orders, doing procedures independently, and a multitude of other requirements.  Our aim was to design a surgical boot camp to help graduating senior medical students feel more confident entering residency.Methods.  A two-week intensive surgery residency prep course was conducted in the spring of 2019 at an Accreditation Council for Graduate Medical Education-accredited General Surgery residency program. The course was designed combining aspects from existing prep courses and innovative ideas tailored to resources available at our institution.  Medical students participated in the Surgery Residency Prep Course as an elective at the end of their fourth year of medical school.  An anonymous survey was given pre- and post-prep course completion evaluating confidence in medical knowledge, clinical skills, and surgical skills.  Data were compared using Wilcoxon Signed-Rank Test.Results.  Six students completed the course as a medical elective.  Students felt more confident at course completion in most aspects, were significantly more confident in all areas of surgical skills taught and evaluated, and nearly all areas of medical knowledge.  Subjectively, students felt as though the course was beneficial and helped them feel more prepared for starting internship.Conclusions.  This course designed at our institution was successful in helping prepare and instill confidence in graduating medical students prior to starting their internship.